Joint pricing and maintenance strategies in availability-based product-service systems under different overhaul conditions. (December 2021) - Jackson, Canek; Pascual, Rodrigo
Abstract: An important increase in maintenance outsourcing is observed nowadays. This is critical for industries that want to focus on core business or cannot perform maintenance in-house. Such is a challenging situation since contracting out implies two parties attempting to maximize their benefits while reaching an agreement at the same time. In this context, a body of research is available regarding maintenance strategies' decision-making. However, contributions related to pricing in maintenance contracts are very scarce. In this work, we propose an original methodology to determine the optimal overhaul and replacement policies for an equipment being maintained by an external agent, while jointly negotiating the service fee. Through the concept of maintenance degree, we study the effect of different overhaul conditions on decision-making for an availability-based contract where both equipment and maintenance are bundled in a single offer. Pricing is determined using a cooperative game approach where bargaining takes place. In particular, a sensitivity analysis is carried out to understand the effect on the number of contracts to serve, the availability service level, the pricing, and the maintenance strategies. A numerical example is presented to illustrate the results. The model was validated using discrete-event simulation over a test case. Highlights: Most organizations outsource a part of their maintenance activities. Optimal contract negotiation requires game-theoretic formulations. Reaching a good service agreement implies cooperation from both parties. Decision-making includes maintenance strategies, served market size and pricing. Different overhaul conditions affect decision-making for both parties.